2020
DOI: 10.15386/mpr-1422
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of oxidative stress in osteoarthritis

Abstract: Osteoarthritis (OA) is a whole joint disease driven by abnormal biomechanics and attendant cell-derived and tissue-derived factors. The disease is multifactorial and polygenic, and its progression is significantly related to oxidative stress and reactive oxygen species (ROS). Augmented ROS generation can cause the damage of structural biomolecules of the joint and, by acting as intracellular signaling component, ROS are associated with various inflammatory responses. By activating several signaling pathways, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 99 publications
2
103
0
2
Order By: Relevance
“…One of these mechanisms was the beginning of oxidative stress as illustrated by marked increase in the serum LPO level in association with marked decrease in the serum GSH level and GST activity. This is in line with the observation of previous report, which found that MIA or its metabolites yield free radicals which attack lipid components, resulting in formation of LPO [ 30 ]. Amplified free radical production from inflammatory site leads to reinforced osteoarthritis and the decreased level of cellular antioxidant [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…One of these mechanisms was the beginning of oxidative stress as illustrated by marked increase in the serum LPO level in association with marked decrease in the serum GSH level and GST activity. This is in line with the observation of previous report, which found that MIA or its metabolites yield free radicals which attack lipid components, resulting in formation of LPO [ 30 ]. Amplified free radical production from inflammatory site leads to reinforced osteoarthritis and the decreased level of cellular antioxidant [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In parallel, the increase in SOD and MDA levels in the serum of osteoarthritic rats has been described [48]. Therapeutic strategies which are able to target the increased ROS represent effective intervention for osteoarthritis driven by oxidative stress [49]. Cashew nuts' oral administration was able to restore GSH and CAT levels and GPx activity in MIA-injected animals.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, BK Ca channels can also be strongly modulated by ‘endogenous ligands’ such as reactive oxygen species (ROS) or estrogen [ 96 ]. It is well known that changes in ROS levels are related to OA [ 97 , 98 ]. When chondrocytes are exposed to various stress such as mechanical stimuli, inflammatory cytokines and hypoxia, ROS including H 2 O 2 , ONOO − , NO, CO and H 2 S is generated.…”
Section: Discussionmentioning
confidence: 99%